Aporte calórico y macronutrimental de los menús infantiles de la comida rápida y convencional - Ramos Peña, Esteban Gilberto; Castro Sánchez, Ana Elisa; Zambrano Moreno, Adriana; Núñez Rocha, Georgina Mayela; Osorio de Dios, Sylvia (2012)
The caloric and macronutrient contribution of the children’s menu in fast food restaurants and conventional restaurants was analyzed, according to mealtimes and recommended intakes for children between 4 and 8 years old in a city in the Northeastern of Mexico with the highest childhood obesity rate in the world. This is an observational, descriptive and transversal study. The sampling was by convenience and directed when typical cases of children’s menus were selected from 152 restaurants. The range of carbohydrates contribution of the children’s menu varied from 53.8% to 97.9% of the recommendation; in any case the protein contribution was less than 82.2%. With regard to fats, contribution ranges were from 63% to 165.3%. These contributions increase considerably when they are analyzed by mealtimes: from 97.8% to 373.4%. In conclusion, fast food and conventional restaurants offer unhealthy meals in big portions to child population.